Effect of audiological testing on programmable ventriculoperitoneal shunts. (1st February 2022) - Abdul-Hamid, Ayeshah; Zilani, Gulam; Bryant, Catriona; Bryant, Alan; Qureishi, Ali; Jeyaretna, Sanjeeva; MacKeith, Samuel
Abstract: Objective: This study aimed at measuring the magnetic field strength of commonly used types of audiological testing equipment and determine their effects on the three most commonly used programmable ventriculoperitoneal (VP) shunts to try and quantify the risk of a VP shunt being reprogrammed during audiological testing. Design: In this in vitro study, magnetic field strength was measured for TDH 39 supra-aural earphones, B71 bone vibrator, ALGO 3i probe, Bio-logic Nav Pro probe, Otodynamics otoport insert earphone and Madsen Zodiac tympanometry probe. Study sample: Magnetic field strength associated with transducers placed on a model of a skulls having implanted Miethke ProGAV 2.0, Medtronic Strata II and Codman Hakim programmable VP shunts was measured. Results: The supra-aural earphones had a magnetic field strength of 14 mT at 0 mm, which dropped to 0 mT at 10 mm away from the transducer. All other equipment had a magnetic field strength of 3.5 mT or less at 0 mm. There was no instance of reprogramming of the shunts by the transducers. Conclusions: The findings suggest that the risk of inadvertent valve-reprogramming by the transducers is extremely small. However, care should be taken to avoid placing any of the transducers directly over the shunt.